2021
DOI: 10.1021/acsaelm.1c00502
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-Derived Carbon-Coated Functional Paper for Printed Electronics

Abstract: Next-generation printed electronics is required to be of high performance, cost-effective, multifunctional, sustainable, and environmentally benign. Herein, we report the manufacturing of a flexible carbon-coated paper for printed electronics ensuring the abovementioned requirements. The multifunctional carboncoated substrate is achieved by employing copy paper, cellulose nanofibers (CNFs), and lignin-derived graphitic carbon as a base substrate, binder, and conductive pigment, respectively, using the scalable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…The one relatively intense peak and another broad peak located at around 22.3° and 43.8° could be attributed to the (002) and (100) reflections of the disordered carbon layer. The high intensity in the low angle region claims the existence of plentiful microporosity within the carbon framework, which is in accord with the nitrogen adsorption–desorption results. …”
Section: Resultsmentioning
confidence: 99%
“…The one relatively intense peak and another broad peak located at around 22.3° and 43.8° could be attributed to the (002) and (100) reflections of the disordered carbon layer. The high intensity in the low angle region claims the existence of plentiful microporosity within the carbon framework, which is in accord with the nitrogen adsorption–desorption results. …”
Section: Resultsmentioning
confidence: 99%
“…[ 277 ] Electrospinning or chemical functionalization can be used for this. [ 178,278 ] Wang et al. created crosslinked electrodes with PVA using lignin and cellulose.…”
Section: Sustainable Materials In Flexible Electronicsmentioning
confidence: 99%
“…[277] Electrospinning or chemical functionalization can be used for this. [178,278] Wang et al created crosslinked electrodes with PVA using lignin and cellulose. One side of this multilayer structure was more rigid and durable, while the other side had high adhesion strength and was more flexible.…”
Section: Complex Natural Organic Mixturesmentioning
confidence: 99%
“…Previous research has shown the potential to produce functional iron oxide materials supported on or encapsulated within hydrochar. For example, carbon-encapsulated nanoparticles have been produced using glucose as the carbon source. , Other work has focused on post-synthesis modification of hydrochars produced from waste lignocellulosic materials through impregnation with an appropriate iron precursor. The latter approach typically requires pyrolysis at temperatures in excess of 600 °C to introduce porosity into carbon. Rattanachueskul et al have demonstrated the conversion of sugarcane bagasse and an iron precursor into magnetic carbon composites via a one-pot synthesis with a 24 h reaction time .…”
Section: Introductionmentioning
confidence: 99%